Development of School Physic Education in Ukraine in 1990-s – Beginning of the XXI Century - Stokratnyi, Serhii (Pedagogical Discourse, 2014)
Main periods of development of school physic education have been considered in the article. As natural-mathematic education, in particular, physics is the important component in personality’s development, it incited the author to choose this topic. School physic education during the mentioned period underwent considerable changes. That is why, having analyzed the development of school physic education, we can compare different stages of development and make some conclusions. The author characterized main changes, which school physic education underwent during the mentioned period of time. The source base on the topic has been analyzed. The researches showed that at the beginning of 1990-s school physic education had been on an adequate level. Such conclusions can be made on the bases of low level of pupils’ knowledge, obsolete textbooks, absence of physical devices, which made impossible any laboratory works. These problems demanded changes of not only school physics, but of the whole system of secondary school education. The article also characterizes the period of introduction of 12-year system of education, which was accompanied by the reconstruction of the system of education, change of curricula, publishing of new textbooks. But, as the time showed, this system didn’t work properly. As a result, changes in education took place again. The author pays much attention to introduction of 12-grade system of knowledge, skills and abilities evaluation. It led to the necessity of changes in the programs and evaluation criteria. Having analyzed the development of school physic education, the author makes conclusions that it is necessary to continue search of essentially new in the theory and practice of studies, to experiment with the curricula on physics which can allow passing to the higher level in education.